MENINGKATKAN KEMAMPUAN OPERASI HITUNG BILANGAN BULAT MELALUI MEDIA MANIK-MANIK BAGI ANAK TUNANETRA KELAS D-4 SLB TUNANETRA PAYAKUMBUH - HEFLINA - (Universitas Negeri Padang, 2015)
Abstract. The purpose of this study was to: 1) Describe the implementation of integer arithmetic operations of learning through the medium of beads, and 2) Prove that the media beads can improve the ability of integer arithmetic operations for visually impaired students of class D-4 SLB Blind Payakumbuh.This type of research is a class act that is performed by the class guruf collaborate with peers on two blind children (MM and MS) D.4 SLB class Blind Payakumbuh. The data obtained through observation, testing and documentation. Then analyzed qualitatively and quantitatively. The results showed that 1) the learning process integer arithmetic operations with media beads made with two cycles. I cycle with five meetings and the second cycle with six sessions. Each cycle begins with the planning, implementation (initial activities, core and end), observation, and analysis and reflection. 2) The results of the study showed that: when the child is still low asessmen ability to obtain the same value, namely one (20). The first cycle of learning the sum of integers (positive and negative) with media beads obtained values for MM (100) and MS (95). Cycle II study subtraction of integers (positive and negative) values obtained for MM (100) and for MS (90) of the 20 questions that tested. Thus, it can be suggested at the school, teachers and researchers can use the media next to the beads in integer arithmetic operations. Kata kunci: Operasi Hitung Bilangan Bulat; Media Manik-manik; Anak Tunanetra